2016
DOI: 10.18632/oncotarget.9174
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between insulin-like growth factor-1 and angiotensin-II in dopaminergic neurons and glial cells: role in neuroinflammation and aging

Abstract: The local renin-angiotensin system (RAS) and insulin-like growth factor 1 (IGF-1) have been involved in longevity, neurodegeneration and aging-related dopaminergic degeneration. However, it is not known whether IGF-1 and angiotensin-II (AII) activate each other. In the present study, AII, via type 1 (AT1) receptors, exacerbated neuroinflammation and dopaminergic cell death. AII, via AT1 receptors, also increased the levels of IGF-1 and IGF-1 receptors in microglial cells. IGF-1 inhibited RAS activity in dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 66 publications
2
49
0
Order By: Relevance
“…Consistent with this, AT1 receptor antagonists reduce proinflammatory microglia activation and promote immunoregulatory microglia polarization (Saavedra, 2012; Rodriguez-Perez et al, 2016; Torika et al, 2016). The classical Ang II/AT1/Nox pro-oxidative and pro-inflammatory axis plays a major role in the RAS effects both in the brain and peripheral tissues.…”
Section: The Role Of Other Angiotensin Receptors In Regulation Of Micmentioning
confidence: 72%
“…Consistent with this, AT1 receptor antagonists reduce proinflammatory microglia activation and promote immunoregulatory microglia polarization (Saavedra, 2012; Rodriguez-Perez et al, 2016; Torika et al, 2016). The classical Ang II/AT1/Nox pro-oxidative and pro-inflammatory axis plays a major role in the RAS effects both in the brain and peripheral tissues.…”
Section: The Role Of Other Angiotensin Receptors In Regulation Of Micmentioning
confidence: 72%
“…We also investigated the effects of gangliosides on the production of microglial IGF-1, a growth factor produced by both neurons and glial cells with neuroprotective, anti-inflammatory and reparative roles [5,60,99]. Microglia is a major source of IGF-1 in the brain [100], especially in conditions that stimulate the acquisition by microglia of an M2-like immunoregulatory/reparative phenotype [101]. We found that expression of IGF-1 mRNA was not affected by exogenous GM1.…”
Section: Discussionmentioning
confidence: 94%
“…Primary mixed glial cultures from P0.5-P1.5 mice (C57BL/6J or FVB/NJ strain) and rats (Sprague Dawley) were prepared following the method described by [46]. In brief, cerebral cortices were enzymatically and mechanically dissociated and cells were seeded in DMEM/F12 medium supplemented with 10% FBS, 100…”
Section: Primary Cultures and Cell Linesmentioning
confidence: 99%
“…In contrast to healthy adult and inflammation‐activated cells, neonatal CD11c + microglia show unique myelinogenic and neurogenic phenotypes (Wlodarczyk et al, ). These cells are the major source of IGF‐1 (Rodriguez‐Perez, Borrajo, Diaz‐Ruiz, Garrido‐Gil, & Labandeira‐Garcia, ), and its selective depletion from CD11c + microglia leads to impairment of primary myelination (Wlodarczyk et al, ). Interestingly, microglia produce and secrete IGF‐1 to support the survival of layer V cortical neurons during postnatal development (Ueno et al, ), yet OLs do this as well (Wilkins, Chandran, & Compston, ).…”
Section: Microglia Neuron and Ol Crosstalk Under Homeostatic Conditmentioning
confidence: 99%